Getting to the Heart of the Matter: Control over the Photolysis of PbI2 Through Partial Lead Substitution - Marina I. Ustinova; Gennadii V. Shilov; Pavel A. Troshin; Sergey M. Aldoshin; Lyubov A. Frolova (Inorganics)
A crucial problem of the photoinduced degradation of perovskite semiconductors based on complex lead halides has been addressed here by suppressing PbI2 photolysis to metallic lead. The systematic screening of >30 modifying cations introduced as substituents for 5% of Pb2+ in the PbI2 composition has revealed their tremendous effects on the rate of material degradation under light exposure. Thus, the most successful stabilizing cations could maintain a high absorbance of the Pb0.95M0.1/nI2 films and block Pb0 formation after 400 h of continuous illumination, when the non-modified PbI2 films completely decomposed to Pb0 and I2. The obtained results present a promising solution for the problem of metallic lead formation in the active layer of perovskite solar cells during their operation, which can pave the way for the development of a new generation of highly efficient and stable perovskite photovoltaics.